First external validity study of the Fagotti score in ovarian cancer - Aida, Sarah; Levaillant, Mathieu; Azaïs, Henri; Ballester, Marcos; Canlorbe, Geoffroy; Chauvet, Pauline; Gauthier, Tristan; Huchon, Cyrille; Kerbage, Yohan; Koskas, Martin; Lecointre, Lise; Ouldamer, Lobna; et al. (Scientific reports, 2024)
Epithelial ovarian cancer is mostly discovered at the stage of peritoneal carcinosis. Complete cytoreductive surgery improves overall survival. The Fagotti score is a predictive score of resectability based on peritoneal laparoscopic exploratory. Our aim was to study the inter-observer concordance in an external validation of the Fagotti score. An observational, prospective, multicenter study was conducted using the Francogyn research network. The primary outcome was inter-observer concordance of the Fagotti score. 15 patients in which an ovarian mass was discovered were included. For each patient, the first exploratory laparoscopy before any treatment/chemotherapy was recorded. This bank of 15 videos was subject to blind review accompanied by a Fagotti score rating by 11 gynecological surgeons specializing in oncology. A total of 165 blind reviews were performed. Inter-observer concordance was very good for the Fagotti score with an intraclass correlation coefficient (ICC) of 0.83 [95% CI 0.71; 0.93]. Inter-observer concordance for the adjusted Fagotti score, which accounts for unexplorable areas with extensive carcinomatosis, resulted in an ICC of 0.64 [95% CI 0.46; 0.82]. According to the reviewers, the three least explorable parameters were mesentery involvement, stomach infiltration and liver damage. The ICC of the explorable Fagotti score, i.e. score with deletion of the parameters most often unexplored by laparoscopy, was 0.86 [0.75–0.94]. This study confirms the reproducibility of the Fagotti score during first assessment laparoscopies in cases of advanced ovarian cancer. The explorable Fagotti score has an equivalent or better inter-observer concordance than the Fagotti score.